Population ecology a unified study of animals and plants - Begon, Michael (Blackwell Science, 2009)
This text examines ecological processes that determine the size and structure of a population. It is designed to be readily understood by undergraduates with little or no previous knowledge of the subject, and also to stimulate wider debate.